2012
DOI: 10.4103/2229-3485.100657
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of HIV-infected patients on antiretroviral therapy regarding adverse drug reactions (ADRs) in selected hospitals in Nigeria

Abstract: Purpose:The study evaluated the knowledge and attitudes of HIV-infected patients on ART regarding ADRs following routine patient counseling and education in selected hospitals in Nigeria.Materials and Methods:From 36,459 HIV-infected patients on ART in the 36 selected hospitals, a study-specific instrument was administered to 3,650 patients in a cross-sectional study. Patients were provided counseling and education on ADRs before and after commencing ART. Factor analysis was performed using principal component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 17 publications
3
15
3
Order By: Relevance
“…This is contrary to a study reported by Agu et al in 2012 which found that knowledge of AEs was associated with female gender, self-employment status and older age [21]. This might be due to the low numbers in our sample size as compared with the multi-centre approach incorporating over 2329 patients from 36 public hospitals reported by Agu et al [21]. Out of 98 participants, 80 (82%) were willing to report their AEs to their healthcare provider in the hospital, but 6 (6%) indicated they will take another drug to treat suspected AEs on their own as against 5 (5%) who preferred to relax and do nothing.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…This is contrary to a study reported by Agu et al in 2012 which found that knowledge of AEs was associated with female gender, self-employment status and older age [21]. This might be due to the low numbers in our sample size as compared with the multi-centre approach incorporating over 2329 patients from 36 public hospitals reported by Agu et al [21]. Out of 98 participants, 80 (82%) were willing to report their AEs to their healthcare provider in the hospital, but 6 (6%) indicated they will take another drug to treat suspected AEs on their own as against 5 (5%) who preferred to relax and do nothing.…”
Section: Discussioncontrasting
confidence: 56%
“…All the measured socio-demographic characteristics of the study participants were found not to be associated with knowledge of AEs. This is contrary to a study reported by Agu et al in 2012 which found that knowledge of AEs was associated with female gender, self-employment status and older age [21]. This might be due to the low numbers in our sample size as compared with the multi-centre approach incorporating over 2329 patients from 36 public hospitals reported by Agu et al [21].…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations